Literasi Pergaulan Halal bagi Mahasiswa Ma’had Al-Jami’ah dalam Menyongsong Generasi Muslim Cerdas Digital - Amalia, Usnul; Septiana, Riska; Septiani, Riski; Mufidah, Naila; Putri, Cantikka Febiriyadi; Rahmawati, Ferida (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to raise awareness among students of Ma'had Al-Jami'ah UIN K.H. Abdurrahman Wahid Pekalongan regarding the importance of implementing halal social values in daily life, particularly in the use of social media. Education is provided to introduce sharia boundaries in digital interactions, recognize deviant forms of social interactions, and teach healthy communication strategies according to Islamic teachings amidst the rapid flow of digitalization. This program is implemented with a service learning approach through four stages: investigation, preparation, implementation, and reflection. The results of the activity show an increase in students' knowledge and awareness of the importance of sharia principles in digital interactions. This socialization is considered effective and is expected to be expanded to reach more young generations, so that they are able to build intelligent, moral, and competitive Muslim characters in the digital era.